Recent grazing reduces reptile richness but historic grazing filters reptiles based on their functional traits. Issue 4 (30th January 2019) - Val, James; Travers, Samantha K.; Oliver, Ian; Koen, Terry B.; Eldridge, David J.
Abstract: Grazing by mammalian herbivores can alter vegetation structure and composition. It can therefore affect critical habitat features used by native wildlife for shelter, feeding, and breeding. This can have variable effects, which advantage or disadvantage particular species, depending on habitat requirements. We tested the relative effects of recent and historic livestock grazing and recent rabbit and kangaroo grazing on all reptiles, and on specific groups of reptiles based on three functional traits: habitat preference (semi‐arboreal, terrestrial, fossorial), activity pattern (diurnal, nocturnal), and primary foraging habitat (tree, litter, open). We used structural equation modelling to assess the direct and indirect impacts of mammalian herbivores (livestock, and free‐ranging kangaroos and rabbits) on reptile richness at 108 semi‐arid woodland sites in eastern Australia. We used a trait‐based approach to classify reptiles according to their: (a) habitat preference, (b) activity pattern, and (c) foraging preference. We recorded 42 reptile species from 1, 736 specimens caught over 13, 824 trap nights. Sites grazed by rabbits were associated with greater richness of semi‐arboreal species. Kangaroo grazing had virtually no effects on total richness or richness within trait groups. The effects of recent and historic livestock grazing differed among reptile trait groups. Increasing intensity of recent livestock grazing reduced the richness of most reptile groups directly, and indirectly suppressed the positive effect of native plant richness on reptile richness. The effects of historic livestock grazing, however, filtered reptiles based on their traits, reducing the richness of tree‐shrub foraging reptiles only. Increasing woody cover had direct suppressive effects on all reptiles, but particularly open foragers and terrestrial species. Overall, the effects of recent livestock grazing were stronger than those of plant richness or woody cover. Synthesis and applications . We demonstrate how grazing by all herbivores, both domestic and free‐ranging, needs to be managed according to seasonal conditions in order to meet the conservation needs of semi‐arid reptiles within landscapes dominated by livestock. Abstract : We demonstrate how grazing by all herbivores, both domestic and free‐ranging, needs to be managed according to seasonal conditions in order to meet the conservation needs of semi‐arid reptiles within landscapes dominated by livestock.